Gilletianus seqalu (Coleoptera: Scarabaeidae: Aphodiinae), a new species from Taiwan - Ho, Bin-Hong; Král, David (Zootaxa, 2025)
Gilletianus seqalu Ho & Král, sp. nov., is described from Taiwan. Relevant morphological characters are illustrated, including epipharyx and male genitalia. The new species is compared species of this genus. Reports in the literature on the occurrence of other species of the genus Gilletianus Balthasar, 1933 from Taiwan are critically reviewed.